The Modified Sternoplasty: A Novel Surgical Technique for Treating Mediastinitis. Issue 4 (29th April 2022) - Kachel, Erez; Arazi, Mattan; Grosman-Rimon, Liza; Yehezkeel, Shachar; Rimon, Jordan; Gohari, Jacob; Shinfeld, Amihay; Sternik, Leonid; Raanani, Ehud; Moshkovitz, Yaron
Abstract : Summary: Deep sternal wound infection (DSWI) is one of the most complex and devastating complications post cardiac surgery. We present here the modified sternoplasty, a novel surgical technique for treating DSWI post cardiac surgery. The modified sternoplasty includes debridement and sternal refixation via bilateral longitudinal stainless-steel wires that are placed parasternally along the ribs at the midclavicular or anterior axillary line, followed by six to eight horizontal stainless-steel wires that are anchored laterally and directly into the ribs. On top of that solid structure, wound reconstruction is performed by the use of bilateral pectoralis muscle flaps followed by subcutaneous tissue and skin closure. We reported mortality rates and length of hospitalization of patients who underwent the modified sternoplasty. In total, 68 patients underwent the modified sternoplasty. Two of these critically ill patients died (2.9%). The average length of hospitalization from the diagnosis of DSWI was 24.63 ± 22.09 days. The modified sternoplasty for treating DSWI is a more complex surgery compared with other conventional sternoplasty techniques. However, this technique was demonstrated to be more effective, having a lower rate of mortality, and having a length of hospitalization lower than or comparable to other techniques previously reported in the literature.